One Health alert: zoonotic scabies from dromedary camels—A case report and call for vigilance - Christiana, Hebel; Rolf Karl, Schuster; Joerg, Kinne; Ulrich, Wernery (Frontiers in Veterinary Science, 2025)
This case report describes the rapid transmission of sarcoptic mange, a highly contagious skin disease caused by the mite Sarcoptes scabiei, from one dromedary camel to a group of other dromedary camels and a group of human beings despite wearing personal protective equipment. This is the first report on an outbreak of human pseudoscabies in the United Arab Emirates, and it highlights the importance of a One Health approach managing zoonotic diseases. Early detection, treatment of infected animals, as well as adherence to hygiene and quarantine protocols are crucial to prevent zoonotic spillovers.